Consumer perception of snack sausages enriched with umami-tasting meat protein hydrolysates. (April 2019) - Kessler, Fabienne; Nielsen, Mathias Boe Riisgaard; Tøstesen, Marie; Duelund, Lars; Clausen, Mathias P.; Giacalone, Davide
Abstract: Adequate protein intake is necessary to maintain muscle mass and function. Nutritionally dense(r) products are increasingly sought after by consumers that need a heightened protein intake, such as active young and elderly individuals. This paper focuses on functional snack sausages enriched with umami-tasting meat protein hydrolysates (MPH), developed by systematically varying in recipe, meat type and MPH content. A consumer study ( N = 100) was conducted where young and elderly consumers evaluated perceived acceptability and sensory quality of samples. Additionally, textural (Warner–Braztler shear test) and chemical (amino acids) analyses on the same samples were conducted to give a complete characterization of the functionality of the hydrolysates. Both the consumer test and the instrumental analyses consistently indicated that the enrichment with MPH had minor or no influence on the perceptual quality of the sausages, suggesting that this ingredient can be added to increase the nutritional density of a reference meat product without negatively affecting consumer acceptability. Highlights: The effect of enrichment with meat protein hydrolysates (MPH) on the perceptual quality of snack sausages is investigated. We report sensory, textural and compositional changes following MPH enrichment in sausages varying in meat type and recipe. Compared to other design factors, enrichment with MPH had minor or no influence on the perceptual quality of the sausages. Drivers of consumer liking and implications for product formulations using MPH as functional ingredient are discussed.